Synthesis of Peculiar Structure of Hydroxyapatite Nanorods by Hydrothermal Condition for Biomedical Applications: Synthesis of hydroxyapatite nanorads - Saheb Ali Manafi,; Sareh Khani,; Atefeh Soltanmoradi, (Iranian Journal of Pharmaceutical Sciences, 2011)
In the present work, the effect of Ca(NO3)2.4H2O and (NH4)2HPO4 primary solutions as the beginning materials in synthesis of a calcium phosphate phase, was examined. So, we investigated the wet chemical reactions in solution at different temperatures by a hydrothermal condition aimed at hydroxyapatite (Ca10(PO4)6(OH)2); (HAp) synthesis. The powders were investigated by XRD, SEM, FE-TEM, HRTEM, EDAX, SAED and FT-IR. It was found that HAp has a length of approximately several micrometres and a diameter of 20-30 nm with different morphologies. As a matter of fact, the method of hydrothermal method guarantees the production of HAs for different applications especially clinical applications.